Disentangling participation through time and interaction spaces–the case of IT design for energy demand management. Issue 1 (2nd January 2018) - Poderi, Giacomo; Bettega, Mela; Capaccioli, Andrea; D'Andrea, Vincenzo
Abstract: Participatory Design has recently seen growing interest in developing critical forms of reflexivity able to disentangle the complexity of participatory ensembles. This article makes a methodological contribution to this endeavour. Drawing on socio-cognitive analyses of collaborative design, it proposes the frame of 'interaction spaces' as a scaffolding tool for conducting retrospective analyses of participatory design processes. The paper uses the 'interaction spaces' frame to analyse the three years of collaborative activities of the CIVIS Project. Through a longitudinal and multi-dimensional account of participatory dynamics involved in the designing, prototyping and testing of an IT platform for home energy management, the frame evidences how participatory configurations evolve over time; it makes clearer the characteristics of participation as partial and overtaken; and it identifies moments of cross-participation as potential basis for the boundary-spanning of design issues.